Compartmentalization and Regulation of Mitochondrial Function by Methionine Sulfoxide Reductases in Yeast - Kaya, Alaattin (2010)
Elevated levels of reactive oxygen species can damage proteins. Sulfur-containing amino acid residues, cysteine and methionine, are particularly susceptible to such damage. Various enzymes evolved to protect proteins or repair oxidized residues, including methionine sulfoxide reductases MsrA and MsrB, which reduce methionine-S-sulfoxide (Met-SO), and methionine-R-sulfoxide (Met-RO) residues, respectively, back to methionine. Here, we show that MsrA and MsrB are involved in the regulation of mitochondrial function. Saccharomyces cerevisiae mutant cells lacking MsrA, MsrB or both proteins, had normal levels of mitochondria, but lower levels of cytochrome c and fewer respiration-competent mitochondria. The growth of single MsrA or MsrB mutants on respiratory carbon sources was inhibited, and that of the double mutant was severely compromised, indicating impairment of mitochondrial function. Although MsrA and MsrB are thought to have similar roles in oxidative protein repair each targeting a diastereomer of methionine sulfoxide, their deletion resulted in different phenotypes. GFP fusions of MsrA and MsrB showed different localization patterns and primarily localized to cytoplasm and mitochondria, respectively. This finding agreed with compartment-specific enrichment of MsrA and MsrB activities. These results show that oxidative stress contributes to mitochondrial dysfunction through oxidation of methionine residues in proteins located in different cellular compartments.